OP0341 Can pain in hand osteoarthritis be associated with mri collateral ligament abnormalities?. (15th June 2017) - Tan, AL; D'Agostino, M-A; Hensor, E; Grainger, A; Emery, P; McGonagle, D
Abstract : Background: Many patients with hand osteoarthritis (OA) have little symptoms. Bone oedema and synovitis have been associated to pain in OA, but inflammation involving ligaments has not been studied, likely limited by inadequate MRI resolution. We have previously found significant ligament pathology in early and established hand OA (HOA) [1]. Objectives: We hypothesise that the well innervated ligaments are key to a better understanding of the relationship between joint structure and pain in HOA. This research aims to see if small joint collateral ligament abnormalities are worth exploring further in relationship to pain in HOA. Methods: High-resolution contrast enhanced MRI of 26 joints in 15 patients (mean (SD) age 58.3 (8.2), 13F:2M) and 10 in 5 healthy controls (age 38 (5.6); 4F:1M) were scanned using a microscopy MRI coil. 15 joints in 8 patients were painful [median (IQR) pain VAS 4 (3, 7)). Joints were scored blinded to clinical data for joint fluid, capsule/synovitis, extracapsular oedema, collateral ligament thickening/oedema/degeneration, extensor and flexor tendons, bone oedema and cysts. All structures were graded 0–3 for normal, mild, moderate, severe, as defined in OMERACT HOAMRIS where available [2]. Proportions of joints with any level of abnormality (score>0) were calculated according to pain status (present/absent). Results: All OA patients with and without pain had ligament abnormalities. Substantive differences in proportion of joints between healthy controls and OA patients were seen for all pathologies except tendons (no tendon abnormalities were found in all groups). Proportions of joints with capsular/synovium, extra capsular changes and proximal cysts differed between OA joints with and without pain but no substantive differences in pathology score were found. Of painful joints, 93% (14) had both ligament and capsular/synovium or extracapsular abnormality present, compared to 45% (5) of non-painful joints. Conclusions: Modifiable abnormalities involving capsular/synovium and extracapsular areas may be more frequently seen in painful OA joints. The presence of collateral ligament abnormalities in HOA joints, whether painful or not, suggest that the severity of ligament abnormalities in small joint OA and the degree of pain may be an important area to investigate further. References: Tan AL, et al. Ann Rheum Dis. 2006 Oct;65(10):1267–72. Haugen IK, et al. J Rheumatol. 2014 Feb;41(2):386–91. Acknowledgements: Funded by NIHR. Disclosure of Interest: None declared